Interception loss canopy cover, C formulation theory / Azinoor Azida Abu Bakar … [et al.] - Abu Bakar, Azinoor Azida; Baki, Aminuddin; Yusop, Zulkifli; Ali, Mohd. Fozi; Khalil, Muhammad Khairudin; Atan, Ismail; Abd. Latif, Zulkiflee (Research Management Institute (RMI), 2013)
The interception phenomenon is normally considered as one of the losses in hydrological cycle that comes into intention of many hydrologists for several decades. The total amount of interception loss is quite limited in storm events, especially in those which cause flooding. However, it is a very important process from the viewpoints of water resources management and energy exchange near the ground surface. Since the interception losses are geographically variable, there are no established standard field methods especially for the forest-based case studies. Most of the interception models obtained the data from the standard meteorological data, and from the literature, indirect methods and direct methods. But there are many flaws to the methods and the data that makes the model underestimates or overestimates the interception. Clearly, it is important to prepare a good data to determine the interception…